Diverse evolutionary pathways of spheroidal asteroids driven by rotation rate - Yuta Shimizu; Hideaki Miyamoto; Patrick Michel (Scientific Reports)
Abstract Asteroids preserve a continuous record of evolutionary processes since the early solar system. They can take various shapes that represent the cumulative results of their evolution. However, for those showing common characteristics, this does not mean that they followed the same evolutionary path. Here, we show that (101955) Bennu and (162173) Ryugu, two near-Earth asteroids with spheroidal shapes, have evolved through distinct pathways despite their similar shapes. Using high-resolution imagery from NASA’s OSIRIS-REx and JAXA’s Hayabusa2 spacecraft, we map ~ 200,000 boulders and find latitudinal particle size sorting on both bodies. This represents opposite directions of surface material movements driven by their different rotation periods (4.3 h for Bennu and 7.6 h for Ryugu): toward the equator on Bennu and toward the poles on Ryugu. Furthermore, the spatial distribution of large boulders on Bennu suggests a prior slower rotation (> 5 h), implying a past shape evolution similar to that of Ryugu. Our findings demonstrate that small variations in rotation period, on the scale of a few hours, can drastically change the gravitational field on an asteroid, sometimes even reversing local gravity direction. This drives complex and diverse evolutionary pathways of asteroids, resulting in top-shaped bodies and binary systems observed today.